The Effect of Hook Size, Spinner Colour and Fishing Season on Catching Efficiency in Angling for Rainbow Trout, Oncorhynchus mykiss (Walbaum, 1792) - Atessahin, Tuncay; Cilbiz, Mehmet (Zoological Soc Pakistan, 2019)
In this study, we aimed to determine the effects of hook size, spinner colour and fishing season on catching efficiency in angling for rainbow trout in Karakaya Dam Lake (Malatya, Turkey). Field studies were conducted monthly for a total of 48 fishing operations between May 2013 and April 2014 and again from January 2015 to December 2015. Fishing activities were carried out using fishing gear with three spinner colours (yellow, blue or red), three hook sizes (No. 2: 2 cm; No. 3: 3 cm; or No. 4: 4 cm) and in different seasons (spring, summer, autumn or winter) by three anglers. At the end of the study, 336 rainbow trout, 13.2-56.5 cm in length and 28.6-2,174.6 g in weight, were caught. The most efficient season for catching fish was in the winter. The mean catch per unit effort (CPUE) values for red, blue and yellow coloured spinners were 0.108, 0.051 and 0.036, respectively. The mean CPUE values for No. 2, No. 3 and No. 4 hooks were 0.049, 0.088 and 0.066, respectively. The mean yield per unit effort (YPUE) for No. 2, No. 3 and No. 4 hooks were 9.88, 24.13 and 19.78, respectively (p < 0.05). In conclusion, we recommend using No. 3-sized hooks in the winter season for maximum fishing efficiency of rainbow trout in Karakaya Dam Lake.
Keywords: Different colour; Spinner; Angling; CPUE; YPUE